2019
DOI: 10.1039/c8sc03033b
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional vs. two-dimensional proton transport processes at solid–liquid zinc-oxide–water interfaces

Abstract: Neural network molecular dynamics simulations unravel the long-range proton transport properties of ZnO–water interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 53 publications
4
68
0
Order By: Relevance
“…Several authors have demonstrated the DNNs' ability to reproduce the complex PES of ab initio potentials, [32][33][34] thus allowing accurate long-time simulations of several condensed phase systems [35][36][37] including metal oxide-water interfaces. 38,39 In the present study, the ab initio-based DNN potential reproduces energy and atomic forces obtained from DFT at a ve orders of magnitude lower computational cost. This allows us to carry out MD simulations at the nanosecond timescale on systems of thousands of atoms and to use enhanced sampling techniques to obtain converged free energy surfaces of proton transfer at the aqueous anatase (101) interface as a function of suitable reaction coordinates.…”
Section: Introductionmentioning
confidence: 85%
“…Several authors have demonstrated the DNNs' ability to reproduce the complex PES of ab initio potentials, [32][33][34] thus allowing accurate long-time simulations of several condensed phase systems [35][36][37] including metal oxide-water interfaces. 38,39 In the present study, the ab initio-based DNN potential reproduces energy and atomic forces obtained from DFT at a ve orders of magnitude lower computational cost. This allows us to carry out MD simulations at the nanosecond timescale on systems of thousands of atoms and to use enhanced sampling techniques to obtain converged free energy surfaces of proton transfer at the aqueous anatase (101) interface as a function of suitable reaction coordinates.…”
Section: Introductionmentioning
confidence: 85%
“…In the condensed phase, water molecules organize themselves into large cluster structures, strongly connected by hydrogen-bond networks [25,26]. Frequently (aqueous) solvated semiconductor surfaces sustain and enhance the formation of such networks [11,[27][28][29][30], resulting in the ordered formation of surface chains of water molecules. Thus the very well-developed network of H bonds in water plays a fundamental role in not only defining its structural and dynamical properties but also the properties of the material it interacts with [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Copyright (2017) American Chemical Society.) differs from that over ZnO (1010) [98] and also investigated in further detail the structure of the water near ZnO surfaces [99].…”
Section: Transport At Surfaces Interfaces and In Amorphous Phasesmentioning
confidence: 99%